OPEN VERSUS LAPAROSCOPIC CHOLECYSTECTOMY IN ACUTE CHOLECYSTITIS: A SYSTEMATIC REVIEW - Zickrullah, Rachmat (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Acute cholecystitis is an inflammatory disease caused by gallstones that can range from mild to severe, with septic sepsis as a complication. It is the sixth most prevalent gastrointestinal disorder and is responsible for 0.2% to 0.5% of all fatalities. 16% of men and 50% of women in their 70s have gallbladder disease, which is a risk factor. Various treatment modalities, such as open or laparoscopic cholecystectomy, are available.Aim: The purpose of this review is to compare the advantages and disadvantages of open cholecystectomy and laparoscopic cholecystectomy in the acute management of cholestitis.Methods: We conducted a comprehensive search of multiple electronic reference databases (PubMed, ScienceDirect, Web of Science, and Cochrane). The inclusion criteria were English-language articles with full-text availability and articles published between 2018 and 2023. The studies analyzed complications and a variety of other parameters to determine the benefits and drawbacks of each method.Results : A total of 5 studies were included. Various complications can be used as parameters to determine the superiority of each method. Four out of 5 studies found that laparoscopic was superior to open cholecystectomy. The hospitalization time of laparoscopic patients was lower (LC 1.67±0.9 days; OC 3.2±1.8) with a lower amount of bleeding during surgery >100 ml compared to open laparoscopic (Intra operative bleeding (OC (n=8) vs LC (n=0)).Conclusion: Considering the advantages and disadvantages of the described complication parameters, laparoscopic procedures are superior and preferable to the use of open cholesistectomy in cases of acute cholesystitis.